PENGARUH MODEL DIRECT INSTRUCTION KOMBINASI MULTIMEDIA TERHADAP PEMAHAMAN KONSEP FISIKA SISWA - Safitri, Baiq Rina Amalia; Ahzan, Sukainil; Sukroyanti, Baiq Azmi (Jurnal Ilmiah IKIP Mataram, 2018)
This study aims to determine the effect of direct instruction model of multimedia combination on understanding of physics concept. The type of research used in this study is quasi experimental and design in this research is pretest-post-test control group design. The research was conducted in class XI MA DI Putri Nurul Hakim. The sample of the research was class XI IPA 1 as experimental class and XI IPA 2 as control class. The data were collected using a motivation questionnaire and a concept comprehension test sheet on Optical materials. Based on the hypothesis test obtained tcount (3.26) is greater than ttable (2.02) so that Ha is accepted. Based on it can be concluded that there is influence of direct instruction model of combination of multimedia to understanding of physics concept of student